The Valuation of Risk Assets and the Selection of Risky Investments in Stock Portfolios and Capital Budgets - Lintner, John (The Review of Economics and Statistics, 1965)
John Lintner, The Valuation of Risk Assets and the Selection of Risky Investments in Stock Portfolios and Capital Budgets, The Review of Economics and Statistics, Vol. 47, No. 1 (Feb., 1965), pp. 13-37